Efficiency droop suppression of distance-engineered surface plasmon-coupled photoluminescence in GaN-based quantum well LEDs - Yufeng Li; Shuai Wang; Xilin Su; Weihan Tang; Qiang Li; Maofeng Guo; Ye Zhang; Minyan Zhang; Feng Yun; Xun Hou (AIP Advances, 2017)
Ag coated microgroove with extreme large aspect-ratio of 500:1 was fabricated on p-GaN capping layer to investigate the coupling behavior between quantum wells and surface plasmon in highly spatial resolution. Significant photoluminescence enhancement was observed when the distance between Ag film and QWs was reduced from 220 nm to about 20 nm. A maximum enhancement ratio of 18-fold was achieved at the groove bottom where the surface plasmonic coupling was considered the strongest. Such enhancement ratio was found highly affected by the excitation power density. It also shows high correlation to the internal quantum efficiency as a function of coupling effect and a maximum Purcell Factor of 1.75 was estimated at maximum coupling effect, which matches number calculated independently from the time-resolved photoluminescence measurement. With such Purcell Factor, the efficiency was greatly enhanced and the droop was significantly suppressed.